Development and initial validation of a creative self-efficacy scale for undergraduates: categorical confirmatory factor analysis and multidimensional item response theory - Abulela, Mohammed A. A. (Frontiers in Education, 2024)
Creative self-efficacy (CSE) has recently received much attention due to its association with student learning and creativity. To that end, a CSE scale was developed for undergraduates and sources of validity evidence based on scale content, response processes, and internal structure were collected. Score reliability, using categorical omega based on the categorical confirmatory factor analysis model and marginal reliability for response pattern scores based on item response theory (IRT), were estimated. After various revision iterations of the initial 28-item pool by 10 subject matter experts and 18 undergraduates, some items were revised, four items were dropped, and ultimately 24 items were field tested for measuring two hypothesized dimensions of CSE among 602 undergraduates. Categorical confirmatory factor analysis results indicated that the two-dimensional model had better fit. Similarly, between the two competing multidimensional IRT models, the two-dimensional graded response model had the best fit. Categorical omega coefficients and marginal reliability for response pattern scores were respectively .88 and .81 for the two underlying dimensions.